Assessment of Clinical Analgesic Levels and Serum Biomarkers in Patients with Rheumatoid Arthritis: A Randomized Controlled Trial Comparing the Efficacy of Diclofenac and Methotrexate Combined Therapy with Extracorporeal Shockwave Therapy - Mei Zhang; Zhongyuan Ma; Rinkiko Suguro; Menglin Zhu; Esther Xinyi Chen; Xin Dong; Meixiu Chen; Linling Cheng; Bolun Su; Yizhun Zhu (Pain Research and Management)
Background. Rheumatoid arthritis (RA) is one of the most common forms of arthritis. Extracorporeal shockwave therapy (ESWT) has been identified as a viable alternative therapeutic approach in light of the present protracted clinical course of pharmacological treatment, and changes in levels of marker proteins in the blood samples of RA patients can be utilized to assess treatment outcomes. Methods. A randomized controlled trial was conducted involving forty patients diagnosed with rheumatoid arthritis (RA) who were assigned randomly to two groups. The first group received a combination of diclofenac and methotrexate (MTX) consisting of 25 mg of diclofenac administered thrice daily and 15 mg of MTX administered once weekly. Individual follow-up assessments were carried out after 7 and 14 days. Meanwhile, patients in the second group underwent two sessions of Extracorporeal Shockwave Therapy (ESWT), with a 7-day interval between sessions. Evaluations were conducted on day 7 and day 14. Patients who displayed pain control and stability were advised to continue the treatment, whereas those who had inflammation and discomfort were administered specific medications, and their progress was closely monitored until day 28. Blood samples were collected from both groups prior to treatment, after the first treatment, and after the second treatment. Four marker proteins (NRP-1, CELF-6, COX-2, and RGS-1) and two inflammatory cytokines (IL-6 and IL-17) were measured using western blot and RT-PCR techniques. A statistical analysis was conducted on the levels of specific proteins and inflammatory factors before and after treatment to evaluate its impact. Result. Both groups exhibited statistically significant differences in the serum level of target biomarkers before and after the intervention. However, the ESWT group demonstrated a more noticeable effect, while the diclofenac + MTX group exhibited a delayed anti-inflammatory effect compared to ESWT. Conclusion. Both treatments significantly improved joint function, relieved pain, and reduced inflammation in patients. However, ESWT demonstrated a more prominent clinical analgesic effect compared to the combination treatment of diclofenac and MTX. Furthermore, ESWT produced a more immediate and noteworthy anti-inflammatory impact by regulating NRP-1 expression, a trophic factor receptor that facilitates vascular endothelial cell migration and tissue repair through angiogenesis, and regulating RGS-1 to limit inflammatory signal transmission and immune cell activation.